Reconstruction of a Kinetic Model of the Chromatophore Vesicles from Rhodobacter sphaeroides - Geyer, Tihamér (Biophysical Society, 2006)
We present a molecular model of a chromatophore vesicle from Rhodobacter sphaeroides. These vesicles are ideal benchmark systems for molecular and systemic simulations, because they have been well studied, they are small, and they are naturally separated from their cellular environment. To set up a photosynthetic chain working under steady-state conditions, we compiled from the experimental literature the specific activities and geometries that have been determined for their constituents. This data then allowed defining the stoichiometries for all membrane proteins. This article contains the kinetic part of the reconstructed model, while the spatial reconstruction is presented in a companion article. By considering the transport properties of the Cytochrome c(2) and ubiquinone pools, we show that their size and oxidation states allow for an efficient buffering of the statistical fluctuations that arise from the small size of the vesicles. Stoichiometric and kinetic considerations indicate that a typical chromatophore vesicle of Rb. sphaeroides with a diameter of 45 nm should contain approximately five bc(1) monomers.